Displacement-length ratios and contractional strains of lunar wrinkle ridges in Mare Serenitatis and Mare Tranquillitatis. (April 2018) - Li, Bo; Ling, Zongcheng; Zhang, Jiang; Chen, Jian; Ni, Yuheng; Liu, Chunli
Abstract: Wrinkle ridges are complex thrust faults commonly found in lunar mare basalts and caused by compressional stresses from both local basin and global Moon. In this paper, we select 59 single wrinkle ridges in Mare Serenitatis and 39 single wrinkle ridges in Mare Tranquillitatis according to WAC mosaic image. For each wrinkle ridge, several topographic profiles near its midpoint are generated to measure its height and maximum displacement ( D max ) through LOLA DEM data. Then we make 2D plots of displacement-length ( L ) for ridge population in the two maria. The D max - L ratios ( γ ) are derived by a linear fit method according to the D - L data. The γ value (2.13 × 10 −2 ) of ridges in Mare Tranquillitatis is higher than the γ value (1.73 × 10 −2 ) of ridges in Mare Serenitatis. In the last, the contractional strains ( ε ) in Mare Serenitatis and Mare Tranquillitatis are estimated to be ∼0.36% and 0.14% (assuming the fault plane dip θ is 25°). The values of the free-air gravity anomalies in Mare Serenitatis range from 78 to 358 mGal higher than those of the gravity anomalies in Mare Tranquillitatis which range from −70 to 120 mGal. The average thickness of basalts in Mare Tranquillitatis is 400 m, while that of basalts in Mare Serenitatis is 798 m. Moreover, the average age for ridge group in Mare Serenitatis is bigger than the wrinkle ridge's age in Mare Tranquillitatis. The formation of ridge group in Mare Serenitatis takes longer time than that in Mare Serenitatis. Therefore, we think the higher value of gravity anomalies, thicker basaltic units and longer formation time for wrinkle ridge in Mare Serenitatis maybe result in the higher value of contractional strain, although the formation of Tranquillitatis basin is earlier than that of Serenitatis basin. Highlights: The D max - L ratios of ridge populations are 2.13 × 10 −2 and 1.73 × 10 −2 for Maria Serenitatis and Tranquillitatis. The contractional strains for ridge populations in Maria Serenitatis and Tranquillitatis are 0.36% and 0.14%. Higher gravity anomaly, thicker basaltic unit and longer formation time may result in bigger contractional strain.